The Portrayal of Racism in The Help Movie - Ni Putu Ratna Paramita Suari; I Gusti Ayu Mahatma Agung; Gek Wulan Novi Utami (EDUPEDIA Publisher, 2026)
Purpose – This study aims to analyze the portrayal of racism in The Help, a film that reflects racial inequality rooted in social systems, everyday interactions, and media representation. Methodology – This research employed a descriptive qualitative design using purposive sampling. The data were selected from spoken dialogues, monologues, and narrative voice in the movie. The data were collected through documentation and note-taking techniques, then identified, classified, and analyzed using Carmichael and Hamilton’s theory of racism. Findings – The findings reveal that Black characters in The Help experience two types of racism, namely individual racism and institutional racism. Individual racism is reflected in direct insults, humiliation, and unequal interpersonal treatment, while institutional racism is represented through social norms, policies, and legal structures that maintain racial segregation and restrict the rights of Black individuals. Novelty – This study contributes to previous research by providing a focused analysis of The Help using Carmichael and Hamilton’s theory, especially in distinguishing racism as both a personal and structural problem. Significance – This study is expected to benefit students, researchers, and educators in literature, film studies, and social studies by improving their understanding of racism as a complex social issue.